2010
DOI: 10.1111/j.1467-873x.2010.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

“We’re Sort of Imposters”: Negotiating Identity at Home and Abroad

Abstract: In this article, I argue that through study abroad programming, university students engage in relational encounters between self (home culture) and other (host culture)-twinned concepts that constitute and are constituted by each other. Moreover, I assert that these encounters take place not only during the students' time abroad, but also well before it as students produce and consume various identities through performances, representations, and discourses. These practices and processes at home shape the ways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Given concerns raised by Talburt (2009), Jewett (2010, and others, I have attempted to reconceptualize Downloaded by [University of Nebraska, Lincoln] at 19:27 24 August 2015 the act of learning in international contexts in light of postcolonial critiques of this phenomenon (Blaut, 1993;Ngugi, 1993;Said, 1993). Previous studies of international professional development have tended to treat border crossings as innocuous occurrences, ignoring or downplaying how the legacy of imperialism frames such interactions.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
See 2 more Smart Citations
“…Given concerns raised by Talburt (2009), Jewett (2010, and others, I have attempted to reconceptualize Downloaded by [University of Nebraska, Lincoln] at 19:27 24 August 2015 the act of learning in international contexts in light of postcolonial critiques of this phenomenon (Blaut, 1993;Ngugi, 1993;Said, 1993). Previous studies of international professional development have tended to treat border crossings as innocuous occurrences, ignoring or downplaying how the legacy of imperialism frames such interactions.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…Talburt's (2009) analysis of one international professional development program in Spain, which utilized Pratt's (2008) postcolonial contact zones as a lens for understanding this experience, suggested that learning through travel is a "dynamic process of potentialities produced at the nexus of multiple places and spaces, presents and pasts, and individual and collective histories" (p. 109). Similarly, Jewett (2010) argued that self (home culture) and other (host culture) constitute and reconstitute each other throughout international professional development. Mahon (2009) came to complimentary conclusions by drawing on theories of poststructuralism and her own "nomadic journey."…”
Section: Rethinking International Professional Development As Teachermentioning
confidence: 98%
See 1 more Smart Citation
“…As such, students of African American descent may go to Africa while students who are of Irish descent may decide to study on exchange in Ireland (Matz ). For example, in Jewett's study of a short‐term study tour with American student to Ireland, participants repeatedly cited their Irish ancestry as “evidence of their Irishness” (, 642). These students claimed their Irish identity through their family heritage.…”
Section: International Student Mobility: Characteristics and Motivationsmentioning
confidence: 99%
“…In addition, many of the discourses associated with study abroad are associated with images of whiteness and privilege (Gore 2005) and notions of reconnecting with ancestral roots (Jewitt 2010), discourses which in particular may conflict with African American identity and historical experience, disenfranchisement, and forced separation from ancestral ties. The view of study abroad as an economic and racialized activity is incredibly strong.…”
Section: Not For People Like Usmentioning
confidence: 99%